Performance Measurement in Local Governments: An Analysis of Organizational Factors - Damayanti, Vadira; Aswar, Khoirul (Information Management and Business Review, 2021)
This study aims to determine the effect of organizational factors, namely decision-making authority, organizational objectives and targets, incentives and technical knowledge on performance measurement. The research sample is the Regional Apparatus of the City of East Jakarta Administration’s Head of Subdivision and Planning Staff. The sampling technique uses the census sampling method. The data analysis method uses Structural Equation Modeling (SEM) using the Smart Partial Least Square application version 3.0. The findings reveal that technical knowledge has a considerable impact on performance measurement. Meanwhile, decision-making authority, organizational objectives and targets, and incentives have no significant effect on performance measurement. The findings of this study have implications for local governments to always maintain a code of ethics according to the standards for the preparation of LAKIP in order to realize effectiveness and efficiency so that government performance in the future can improve.